Cross-Platform Mobile Photogrammetry for Heritage Preservation: Evaluating Low-Cost and Premium Devices in Sustainable Architecture Research: Fotogrametri Seluler Multi-Platform untuk Pelestarian Warisan Budaya: Evaluasi Perangkat Berbiaya Rendah dan Premium dalam Penelitian Arsitektur Berkelanjutan - Dharmatanna, Stephanus Wirawan; Agustianti, Stefani Widya (RUAS, 2025)
Digital heritage preservation is often hampered by high costs and limited access to cutting edge technologies such as laser scanning, especially for communities in developing countries. The emergence of mobile photogrammetry supported by smartphone applications such as Polycam offers a low cost and sophisticated solution for documenting architectural heritage. This study aims to compare the comparative reliability of Android (Samsung A55) and iOS (iPhone 13 Pro with LiDAR) devices in documenting architectural heritage elements in Indonesia. Data collection was conducted by evaluating the comparative features of Polycam on both platforms based on features, image upload capacity, processing time, output quality, and the strength and weaknesses of both platforms. The findings show that Android devices provide more efficient and user-friendly data collection while iPhone (iOS) devices produce more detailed and refined outputs, although the reconstruction process takes longer than Android. This study concludes that cross-platform mobile photogrammetry can play an important role in sustainable architecture research, enabling community based participation and academic exploration. This research positions mobile photogrammetry as a transformative tool for heritage preservation in the era of Society 5.0.